Three Adjacent Transfer RNA Genes in Escherichia coli - Squires, Craig (National Academy of Sciences, 1973)
A defective ϕ80 transducing phage has been isolated that carries a small section of the E. coli chromosome from the region near argH (77 min). This phage contains three E. coli tRNA genes, termed glyTsu(+)(36), tyrT, and thrT. These genes specify the structures of tRNA(2)(Gly) (su(+)(36)) tRNA(2)(Tyr), and tRNA(3)(Thr), respectively. Induction of a single lysogen bearing this phage brings about selective synthesis and amplification of only these three tRNAs.